KOMUNIKASI DALAM MENUNJANG KEPEMIMPINAN KEPALA SEKOLAH DI SEKOLAH DASAR NEGERI 2 KEMUNING BANJARBARU - Faridah Karyati (Pahlawan Jurnal Pendidikan-Sosial-Budaya, 2018)
The purpose of this study is to find out whether the communication in the State Elementary School 2 Kemuning can support the leadership of the principal in terms of communication downwards, namely communication from the principal to teachers, communication to the top of the communication from the teacher to the principal, and communication to the side of  communication between peers. The research method used is survey method with quantitative approach. The population in this study amounted to 18 teachers of the State Elementary School 2 Kemuning which also became the sample of his research. The data digging tool used is the questionnaire as a tool to dig primary data and documentary as a means of digging secondary data. The results of his research indicate that: communication in supporting the leadership of the principal in the State Elementary School 2 Kemuning Banjarbaru a small part is well done so that it can support the leadership of the principal, a small number is also good enough so that it can also support the leadership of the principal, and a few still exist lack of communication is done so less support the leadership of the principal. Viewed from downward communication or communication done by the principal to the teachers found most of the communication is always done, whereas the upward communication or communication done by the teachers to the principal shows that quite large teachers sometimes make communication up , and horizontal communication, communications conducted among colleagues show that a small part is also sometimes done.Based on the above, the communication at State Elementary School 2 Kemuning  Banjarbaru still not optimal in supporting the leadership of the school principal. Therefore, it is suggested that the principal should intensify communication both downwardcommunication, upward communication, and communication to the side with various ways and communication pattern so that with more smooth communication, clear, open and honest, various problems found in the school can be found the solution is right and education in school is more optimal.